Production of tobacco seedlings (Nicotiana tabacum) with two types of substrates and plant extracts based on cinnamon (Cinnamomum verum) and aloe vera (Aloe vera). (Semiárida, 2025)
The production of tobacco seedlings is key to guarantee optimum yields, since healthy and vigorous plants that are adapted to the soil and climatic conditions of tropical regions are required. In this sense, the objective of this work was to evaluate the use of plant extracts combined with substrates on the growth of tobacco (Nicotiana tabacum) seedlings to produce quality seedlings that allow an increase in yields in the field. For this purpose, an experiment was conducted under greenhouse conditions, the experimental design was completely randomized blocks, using six (6) treatments with five (5) replications. The treatments evaluated were type of substrate; peat and mineral soil, as well as vegetable extracts based on cinnamon (Cinnamomum verum) and aloe vera (Aloe vera) and the control. The variables evaluated were: seedling height, chlorophyll, root fresh weight, root dry weight and root volume, substrate temperature and pH. The results found showed that the seedlings with greater development were obtained when plant extracts based on cinnamon and aloe vera were combined with the contribution of nutrients and growth promoting substances, in addition to regulating the adverse effect of abiotic factors such as temperature and pH, so the use of these practices at greenhouse level is an alternative for the sustainable production of healthy tobacco seedlings that ensure optimal post-harvest growth.
Keywords: extracts; organic; sanitation; sustainability; substrates